From Direct to Indirect Monetary Policy Instruments The French Experience Reconsidered - Quintyn, Marc (International Monetary Fund, 1991)
If not carefully planned, the transition to indirect monetary policy instruments may result in a loss of control. The 1967-71 attempt in France failed because of a misconceived instrument-mix and sequencing. Credit controls, reintroduced in 1972, were only formally abolished in 1987. This paper attributes the successful 1987 reform to changes in the policy framework in the 1980s. The interest rate was already the key instrument because direct controls became less effective and because of the priority given to the exchange rate objective. Consequently, the 1987 transition was from pegging to guiding the interest rates. Empirical evidence underpins this interpretation